Revitalisasi, Sebuah Pendekatan Dalam Peremajaan Kawasan - Widjaja Martokusumo (The Institute for Research and Community Services, Institut Teknologi Bandung, 2008)
Revitalisation is indeed an expression of institutionai policy as direct towards the structure of political hegemony and economical policy of a certain period of time. Sociocultural, environment and economic aspects have been the most important elements in creating sustainable environment. In essence, as a process revitalisation is an integrated effort to bring back the vitality of underused and deteriorated urban areas, while as a program it is a part of the urban development approaches. This paper does not intend to differentiate the terminology of renewal, rehabilitation and gentrification, but rather tries to highlight the role and position of revitalization in conjunction with renewal process. As this paper argued, each of terminology has a specific characteristic in urban development. Discussion also highlights the problem of gentrification in urban development process, which might have negative impacts in urban revitalization process. The issue of civil society and people empowerment in urban revitalization have been raised in connection with the democratization of urban planning and development mechanism.